تجليات استدعاء التراث في الشعر الجزائري المعاصر - تغليسية, آسيا (Revues faculté des lettres et des langues; No 18 (2016): مجلة كلية الآداب واللغات)
إن المتصفح للشعر الجزائري المعاصر يلحظ بروز ظاهرة توظيف التراث في قصائد عديدة بشكل لافت للنظر، تقف شاهدا على وجود تجربة فنية جديدة كان لتأثير الحداثة الشعرية السبب في بروزها وتجليها وذلك من خلال أشكال تراثية مختلفة تتدرج عبر مستويات إبداعية من صورة جزئية في قصيدة إلى استغراقها كلية. ومن ثم فقد عمدت إلى معالجة هذه الظاهرة بتناول بعض النماذج لدراسة ما أضافته للنص الشعري على المستوى الفكري والفني صياغة وتعبيرا، والتعرف على قدرة الشاعر في قراءة تراثه قراءة ثانية واستخراج طاقاته الكامنة لاستغلالها في حمل أبعاد تجربته المعاصرة.                   When dealing with the Algerian modern poem, one can strongly notice the prominent folklore usage in many different poems. One can witness that there is a new technical experience that was affected by the poetical modernity. This latter aims at addressing new perspectives through different artistical models. Moreover; it treates this phenomenon by using some models to study what they to the poetic text at both the intellectual and artistic level in terms of structure and expression.  know about the poet´s ability to be aware about his audience and exploit his hidden power to expand his modern experience.